Pengembangan Lembar Kerja Komik Berbasis Android untuk Menumbuhkan Kreativitas Belajar dan Meningkatkat Hasil Belajar Siswa - Astutik, Puji; Elviana, Elviana (Jurnal Nispatti, 2025)
Education in the 4.0 industrial revolution demands teacher creativity in concocting creative and interesting learning activities, especially the use of digital media (gadgets) which are often misused by students. Comic worksheets based on Android are an alternative solution that can be used to solve the problem of using gadgets in students and can add variations to the worksheets that teachers often use in teaching. The purpose of this study was to determine the growth of student learning creativity and the improvement of student learning outcomes after using Android-based comic worksheets in science learning. The design used in this study was a one-group pretest-posttest design, while the development of an Android-based comic worksheet used the 4D model which consisted of 4 stages, namely Define, Design, Develop and Disseminate. Comic worksheets based on Android were tried out in class 7H SMP Negeri 5 Bojonegoro, which consisted of 32 students. Android-based comic worksheet assisted learning has been able to foster student learning creativity with a growth percentage of 82.3% and an increase in learning outcomes with an average N-gain of 0.76 in the high category so it can be concluded that Android-based comic worksheet assisted learning Able to foster student learning creativity and improve student learning outcomes.